Explicit and Implicit Meanings in the Historical Politics of Ukrainian Presidents in 1991-2010 - Jędraszczyk, Katarzyna (Wydawnictwo Naukowe Contact/ABC, 2015)
The reluctance of historians towards the notion of “historical policy” stems from its negative associations with the historical propaganda of the People’s Republic of Poland. The very combination of the words seems an oxymoron to many historians. However, it should be noted that some experts in the field (especially in Germany, though in Poland as well) stress that historical policy can, and even should be approached as a positive phenomenon, particularly in the context of phenomena which benefit identity building and the advancement of thorough historical research. Also, historical policy encompasses institutional undertakings aimed at promoting specific attitudes to history. The style of managing historical policy depends primarily on the stage of development of political culture and the degree to which civil society has developed and (in the case of Ukraine in particular) the stage of the nation-building process. In the latter instance, we are dealing with a vision of nation-building process which heads toward titular or civil nation. Historical policy has also much in common with persuasion-oriented communications. The authority is the communicating entity, and in Ukraine, given his powerful constitutional status, it is the president. Ukrainian society meanwhile are the recipients. The greatest dilemma of Ukraine’s historical policy lies in the marked influence of the split to which ethnic Ukrainian territory was subjected, i.e. the division between tsarist Russia and the Habsburg Empire. This is reflected in the sense of identity and the nature of national transformation. The Dnepr river marks the symbolic dividing line. The omplex past resulted in two historical frameworks and two types of historical narration. Yuri Shapoval defines one as nativist and the other as alternative. Each type offers a singular catalogue of events. In the first narrative, we have Kiev Ruthenia, Principality of Galicia-Volhynia, the noblemen and the Cossacks of the Polish-Lithuanian Commonwealth, the period of rule of the Russian and Austrian-Hungarian empires, the year 1917, the West Ukrainian People’s Republic, People’s Republic of Ukraine, liberation struggle, the Famine, Ukrainian Insurgent Army, dissidents and independence. The alternative narrative comprises different elements: the joint nation of old Ruthenia, Lithuanian-Polish colonisation, the Council of Pereyaslav, social and political movements of the 19th century, October Revolution, the people’s war, Ukrainian Socialist Soviet Republic, the Great Homeland War, fighting against the German invaders, Ukraine a member of the UN, downfall of the USSR as a tragic moment in history. Yaroslav Hrycak calls one vision of history a “Ukrainian, traditional” and the other a “Soviet” one. Both have their pantheons of heroes and, due to linear nature, both are simplifications. Thus, from the beginning of independence, Ukraine has entertained two visions of Ukrainian past which function simultaneously. One may be termed “Ukrainian” and the other “post-Soviet”. The former draws a picture of Russian oppression (as well as Polish-Lithuanian), while recounting tales of heroism, dedication and nationalist sentiments. In the latter, the narrative tells the story of friendship with the Russian nation, their kin in language religion and culture, a friendly nation since times immemorial. In the initial years of independence, Ukrainian authority strove to legitimise and consolidate its position, often patently demonstrating their respect for history. The leaders of independent Ukraine, who originated from the former communist elites, adopted the “national project” (national-democratic), which helped them justify the existence of a new political entity and distinguished the “new Ukraine” from its predecessor. As regards symbols and discourse, the ideological void of the early 1990s was filled with rhetoric which since then would be employed by pro-nation and pro-reform groups, gathered around “Rukh”. The subsequent stage, from 1994 to 2004, is associated with the two terms of president Leonid Kuchma, and largely a rehabilitation of the Soviet legacy of Ukraine. Kuchma came to power as a representative of the historical awareness of eastern and southern Ukraine. With tim.e his policy acquired an ambivalent but also fairly balanced attitude towards the past. The views of president Yushchenko also evolved, though in a different direction. During the campaign, despite the attempts to categorise him as an adherent of the national or even nationalist narrative, he appeared to be for the consensus. However, as time went by, he became an advocate of the slogan “one church, one language, one history”. His actions fuelled the latent discord concerning historical policy. He addressed the most controversial issue which the people of Ukraine are not yet ready to evaluate, namely the role of the Ukrainian Insurgent Army in the history of Ukraine. Undoubtedly, president Yushchenko should be credited with “activation” of the national memory of the 1932-1933 famine and the creation of the Ukrainian Institute of National Remembrance. (2006). As a young state, Ukraine needs good historical policy and prudent support of the state in the process of studying and shaping of the image of its past. The lack of crystallised concept of policy of memory and its changeability are an acutely felt issue. There is no fixed calendar of national holidays and anniversaries which would be important for the Ukrainian citizen, a singular “charter” of memory. However, this is by no means a surprise as each citizen was brought up in a specific historiographic tradition, which still exerts an influence on the historical perception, interpretation and narratives. Unfortunately, history is fairly often a topic exploited for political purposes and a source of social rifts, which the political circles deliberately nurture and fuel. Consequently, it often happens that policy of memory breeds a conflict of memory.
Keywords: historical policy; anniversaries; national holidays; historical narrative; conflict of memory